Evaluación de tres lacto reemplazantes en lechones para prevenir diarreas ocasionadas por Escherichia coli, en Guaranda, provincia Bolívar - Barragán Ocampo, Hernán Bayardo (2024)
The present investigation has as its main objective; use three lacto replacers in piglets to prevent diarrhea caused by Escherichia coli. In the Granary of God Pig Farm belonging to the Province of Bolívar Cantón Guaranda, Paltabamba community, for the use of lacto-replacers, it was necessary to disinfect the entire farrowing area, then the sows were attended to, followed by the variable initial weight, on day two the lacto replacers are applied in the doses indicated by the manufacturer, on the third day the iron is applied to the piglets, later on five days the weekly weight variable is taken, a substitute porridge is also made of milk plus concentrated food so that the piglets get used to solid food and after seven days each one of the piglets is immunized followed by that at ten days of age the male piglets are castrated and as a final part they are proceeds twenty-one days to weaning and taking the final weight and second dose of immunization after all this process we were able to determine that after the analysis of comparison of means treatment two (T2) was the best with the highest mean (7, 94) in weight gain, while treatments three (T3) and treatment one (T1) were similar, while treatment 4 (T4) obtained the lowest mean (5.06). If there was a presence of E. coli in treatments T1, T2 and T3 but they are in a normal range which does not affect the digestive system of the piglets, since these bacteria are in an inactive state and do not alter the microbial flora at all. difference from T4 which turned out to have a high presence of E. coli. The treatments presented highly significant differences in the weight gain variable, with treatment two presenting the best results, however, treatment one and three were equivalent, while treatment four obtained the lowest weight gain.